(untitled) (Journal of Enam Medical College, 2017)
Background: Hepatitis C virus (HCV) infection and chronic kidney disease are common and potentially serious medical problems throughout the world. In recent years, it has become clear that these two conditions are linked in several important ways. Indeed, some forms of renal diseases are precipitated by HCV infection and patients with end-stage renal disease (ESRD) are at increased risk for acquiring HCV infection. Patients with chronic kidney disease typically show an impaired immune response compared with healthy individuals and also other risk factors related with treatment and management. CKD patients ultimately undergo end stage renal therapy like dialysis for their treatment and survival. Risk factors for the infections are more in dialysis period than in predialytic stages. Like other developing countries CKD patients with HCV infection are very common in our country. For this reason the CKD patients should be properly diagnosed knowing the infection status before dialysis which would help both the patient and doctor to choose their proper treatment approach. Objective: This cross-sectional study was done to know the prevalence of HCV infection in the CKD patients before starting dialysis therapy. Materials and Methods: A total of 197 patients with chronic kidney disease stage five (CKD-V) before starting dialysis therapy were included as subjects of this study. Among the CKD patients anti-HCV was detected to see prevalence of hepatitis C virus infection. The patients were also tested for HBsAg to assess co-infection. After collecting all the data of different test results analyses were done by SPSS version 15.0. Results: In this study 195 (99%) patients were anti-HCV negative and only two patients (1%) were found positive. Conclusion: HCV infection in CKD patients before dialysis should be taken into account so that HCV negative CKD patients would not get the infection during dialysis and standard screening procedures should be taken to prevent transmission of infection. J Enam Med Col 2017; 7(1): 20-24